The political power of bad ideas networks, institutions, and the global prohibition wave - Schrad, Mark Lawrence (New York ; Oxford : Oxford University Press, 2010)
In this work, Mark Lawrence Schrad looks on an oddity of modern history - the broad diffusion of temperance legislation in the early 20th century - to make a broad argument about how bad policy ideas achieve international success.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Policy sciences -- Case studies; Culture diffusion -- Political aspects -- Case studies; Prohibition; Temperance; Globalization -- Case studies